Review of empirical models for estimation of dune field characteristics - Gordon Gilja; Neven Kuspilić; Kristina Potočki (Građevinar, 2017)
The paper presents an overview of the current state-of-the art and an approach to the study of dunes by analysing direct generators of physical processes in river beds. The approach is based on velocity measurements for mobile bed characterised by transport of bed load using the acoustic doppler current profiler (ADCP). The influence of mobile bed velocity on morphodynamic processes has remained unexplored to this day.